Sekolah sebagai Rumah Iman Menumbuhkan Spirit Religius dalam Kehidupan Siswa - Syahla Salsabila; Aflahul Anam; Rif’atul Hasanah; Muhammad Syafiurrahman; Abdul Fadhil (Hikmah : Jurnal Studi Pendidikan Agama Islam, 2025)
This article explores the concept of a “House of Faith” as a holistic educational framework designed to build students’ character based on religious values. The fundamental idea of the House of Faith is likened to a school environment that provides a comfortable and safe space for students to develop their faith and noble character through learning activities connected to religious teachings. A religious school environment is created through everyday atmospheres that encourage the practice of worship, the presence of religious symbols, and community activities that strengthen students’ spirituality. Programs to reinforce religious spirit include activities such as communal prayers, religious studies, and social projects designed to gradually enhance students’ spiritual awareness. Teachers and educational staff play a highly effective role, acting as role models and facilitators in the learning process. Their approach to instilling faith and moral values involves interactive methods such as group discussions, inspirational stories, and personal reflection, all adapted to students’ developmental stages. Collaboration between the school and parents becomes a key factor in ensuring consistent support. This is carried out through regular meetings, joint workshops, and open communication that reinforces family values. The impact of religious spirit on students can be seen in increased discipline, social empathy, emotional resilience, and stronger academic motivation. However, implementation faces challenges such as limited curriculum time, diversity of student backgrounds, and cultural resistance. These challenges are addressed through solutions, including regular teacher training, program evaluation, and the integration of technology for distance learning. Overall, the article emphasizes that a school functioning as a House of Faith can shape young generations who are not only intellectually capable but also strong in faith and morals, contributing to a more harmonious and meaningful society.